Effects of solid lubricants on properties of Al-Si-SiC composite powder produced by gas atomization technique - Rudianto, H; Yang, S S; Kim, Y J; Dlouhy, I; Caesarendra, W (Journal of Metals, Materials and Minerals, 2020)
Al-Si-SiC composites powder was analyzed in this research. The powder was made by gas atomizing process. Powder characterization was done to observe its morphology, particle size distribution and thermal properties. Effects of lubricants were intensively investigated in this research with compositions and pressure variables. It is assumed that higher amount of solid lubricant put into the powder, the lower ejection force needed to take out compacted powder. Finding appropriate solid lubricant is necessary to improve green and sintering properties. EBS (ethylene bis stearamide), aluminum stearate, zinc stearate and paraffin wax were used for investigation. Sintering under ultra high purity nitrogen gas 99.9999% was carried out to produce high density material. SEM-EDS and XRD were carried to characterize this powder. SiC particles in this powder prohibit to achieve optimum sintering properties of Al-Si-SiC due to their resistance during compaction which leads to form pores and lower sintering density. And ethylene bis stearamide (EBS) seems to be suitable solid lubricant for this powder by giving lower ejection force, flowability and higher sintering density for 93.5%.